Comprehensive School Safety Initiative, St. Louis County, Missouri, 2016-2019 - Esbensen, Finn-Aage ([Verlag nicht ermittelbar], 2023)
This multi-year study investigated the causes and consequences of school victimization (e.g., property theft, minor assault, bullying, cyberbullying) as well as factors contributing to safe learning environments (e.g., school disciplinary practices, students' willingness to report dangerous behavior, availability and utilization of victim services). The project includes three annual surveys of students initially enrolled in 12 middle schools in St. Louis County; a summer component consisting of semi-structured interviews with a subsample of 197 students, including in-depth interviews with 37 students the following summer; and two surveys of school personnel. There are three areas of interest that guide this project and are associated with better understanding of the root causes and consequences (i.e., correlates) of school violence: (1) Identification of patterns of school violence: the principal investigators surveyed two student cohorts over three years as they transitioned from middle to high school (7th/8th grades to 9th/10th grades) (2) Identification of correlates of school violence relying on multiple sources, including: the individual (e.g., gang membership, attitudes toward violence), the school and school climate (e.g., willingness to report, awareness and utilization of victim services, views on the procedural justice of school disciplinary practices, gang presence at the school) and the situation (e.g., where, when, and with whom violence occurs) (3) A specific examination of bullying and cyberbullying as unique forms of school violence with regard to their correlates stemming from each source identified above